2015
DOI: 10.1590/s1984-29612015076
|View full text |Cite
|
Sign up to set email alerts
|

Application of different techniques to detect Toxoplasma gondii in slaughtered sheep for human consumption

Abstract: The aim of this study was to investigate occurrence of Toxoplasma gondii in sheep slaughtered in the state of Alagoas, Brazil, by means of different diagnosis techniques. Serum samples and tissues from 100 slaughtered sheep were used. To detect antibodies, the indirect immunofluorescence antibody test (IFAT) was used, and tissues from seropositive animals (cut-off ≥1:64) were submitted to Polymerase Chain Reaction (PCR) and immunohistochemistry (IHC). To assess the concordance between the direct techniques, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
2
4
0
2
Order By: Relevance
“…It was found that anti-T. gondii antibody is prevalent in sheep (12.0%) and cattle (8.7%). These fi ndings are almost similar to 14% in sheep (Nunes et al, 2015) and 8.57% in cattle (Azizi et al, 2014). Surprisingly in all the studied species of animals, highly appreciable fi ndings were that female, older age group (above 18 months in sheep and above 5 years in cattle) and pregnant animals were found more susceptible to T. gondii.…”
Section: Discussionsupporting
confidence: 69%
“…It was found that anti-T. gondii antibody is prevalent in sheep (12.0%) and cattle (8.7%). These fi ndings are almost similar to 14% in sheep (Nunes et al, 2015) and 8.57% in cattle (Azizi et al, 2014). Surprisingly in all the studied species of animals, highly appreciable fi ndings were that female, older age group (above 18 months in sheep and above 5 years in cattle) and pregnant animals were found more susceptible to T. gondii.…”
Section: Discussionsupporting
confidence: 69%
“…Similar serological studies conducted in Brazil have also reported seroprevalence values in sheep ranging between 3.7-35.3% SILVA et al, 2003;PINHEIRO JÚNIOR et al, 2009;SOCCOL et al, 2009;PEREIRA et al, 2012;NUNES et al, 2015;SILVA et al, 2015).…”
Section: Introductionsupporting
confidence: 77%
“…Durante o parto foram coletadas amostras de 80 placentas que, inicialmente, foram submetidas ao método rotineiro de processamento e inclusão em parafina e, posteriormente, foram submetidas à análise histopatológica para identificação de lesões compatíveis com Toxoplasma gondii segundo critério estabelecido por Buxton e Finlayson (1986). As amostras placentárias foram analisadas quanto à presença de áreas de necrose, infiltrados mononucleares e áreas de calcificação e, posteriormente, foram submetidas à técnica de IHQ (Pereira-Bueno et al, 2004).…”
Section: Methodsunclassified
“…Um animal positivo no ELISA e no exame histopatológico foi negativo na IHQ. Isso também pode ocorrer devido à presença do parasito em outros tecidos ou em partes do mesmo tecido não analisadas, levando a um resultado falso-negativo na IHQ (Nunes et al, 2015), o que indica a necessidade de coletar vários fragmentos dos órgãos para minimizar esse efeito.…”
Section: Duasunclassified